Sleep Disturbance as a Mediator Between Chronic Skin Diseases and Mental Health Disorders - Chmura, Katarzyna; Bonarska, Marta; Kowalska, Katarzyna; Kwaśniewska, Paulina; Najbar, Joanna; Pyziołek, Marta; Rendaszka, Katarzyna; Stróżna, Małgorzata; Zimnoch, Barbara (Quality in Sport, 2025)
Introduction: Chronic skin diseases impose a multidimensional burden that extends far beyond physical symptoms. Epidemiological evidence consistently reveals a disproportionately high prevalence of psychiatric comorbidities in dermatology patients, particularly anxiety and depression. Historically, the psychological distress observed in this population has been attributed primarily to the psychosocial impact of body image dissatisfaction. However, this perspective is increasingly viewed as incomplete. Emerging research suggests that persistent sleep disturbance acts as a physiological pathway linking cutaneous inflammation to mental health decline, yet its specific role as a functional mediator remains underappreciated. Aim of the study: This review aims to evaluate the evidence supporting sleep disturbance as a key mediator linking cutaneous symptoms to mental health disorders. Materials and method: A narrative literature review was conducted in the PubMed database up to the year 2025. Conclusions: Evidence suggests that nocturnal pruritus cause severe sleep fragmentation and alter sleep architecture, particularly reducing rapid eye movement sleep. This sleep deprivation acts as a primary biological stressor, activating the HPA axis and upregulating pro-inflammatory cytokines, which are shared biomarkers for both cutaneous inflammation and major depressive disorder. Furthermore, sleep loss impairs emotional regulation and lowers the threshold for stress coping, creating a cycle where psychological distress exacerbates skin symptoms. Sleep disturbance is not merely a secondary symptom of skin disease but a critical mediator of psychiatric morbidity. Effective management of chronic skin diseases must include the assessment and restoration of sleep quality. Targeting sleep disruption - through itch control or behavioral interventions - may serve as a potent strategy to prevent the development of secondary mental health problems in dermatological patients.